Respuesta :
Which recursive formula can be used to generate the sequence below, where f(1) = 3 and n ≥ 1?
3, –6, 12, –24, 48
The recursive formula for this sequence is
f (n + 1) = –2 f(n)
at n=1 f(n)= 3
at n = 2
f(2) = -2 (3) = -6
n = 3
f(3) = -2 (-6) = 12 and so on
The recursive formula for the sequence is:
f(n+1) = -2f(n)
Let's take an example:
Let f(n) = 12 and we need to calculate f(n+1) which should be -24
If we apply the formula than the answer is:
f(n+1) = -2*12 = -24.
I hope that this is the answer that you were looking for and it has helped you.
f(n+1) = -2f(n)
Let's take an example:
Let f(n) = 12 and we need to calculate f(n+1) which should be -24
If we apply the formula than the answer is:
f(n+1) = -2*12 = -24.
I hope that this is the answer that you were looking for and it has helped you.